ANALISIS PERKEMBANGAN LINGUISTIK GENERASI ALPHA DI ERA DIGITAL - Sumartini, Ni Luh Putu Unix (Prosiding Seminar Nasional Bahasa Ibu; Vol 2 No 1 (2025): Prosiding Seminar Nasional Bahasa Ibu 2024/2025, 2025)
The linguistic development of generation Alpha is extremely a crucial issue to study, especially in the massive digital era, where the language evolves freely and openly. Children who were born after year of 2010 (Gen A) grown up entirely in a technology-driven environment. This study focuses on understanding the patterns of language use among Gen-A , the impact of digital technology on their language habits, and the role of parents and society in guiding the proper language use. This research uses a literature study method supported by various reliable sources, including content analysis from social media platforms such as Instagram, X, Tiktok, Youtube and others. Social media data provide some insights into chat trends such as the use of slang, the adoption of foreign words, and the simplification of communication among Generation Alpha. The findings reveal that the digital technology has both positive and negative impacts. Positively this trend enhances multilingual skills through language-learning applications. However, it also poses challenges for the Indonesian language, such as the decline of formal and regional language use, a lack of understanding of proper linguistic rules, and other related issues. Parental and societal guidance plays a crucial role in providing direction, mitigating negative impacts, and strengthening literacy skills and appreciation for the Indonesian language. This paper offers strategic recommendations to support the linguistic development of Gen-A amid the rapid evolution of the digital era.